Advancing Ocular Health Through Interdisciplinary Collaboration: Nursing, Ophthalmology and Epidemiology Strategies - (6), Belgith Ali Saad Alshekiy (7), Amnah Maqbulal Alawi (8), Hasan Mohamad Altaweel (9), Hamad Abdullah Albrahim (10), Azzam Abdulaziz Alsenan (11), Majid Hamad Ali Al-Sanani (12)., Hasan Issa Alfaqih (1), Halimah Yassin Alaamri (2), Shaya Nehari Algubishi (3), Alyya Hussein Almarhabi (4), Halima Shaybah Zaid Almaqadi (5), Amnah Ali Hassan Alreshy (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Ocular health plays a pivotal role in maintaining overall well-being and quality of life. To address the complex challenges associated with ocular health, interdisciplinary collaboration between nursing, ophthalmology, and epidemiology has emerged as a crucial strategy. This collaborative approach brings together professionals from diverse backgrounds to enhance knowledge, improve patient care, and develop innovative strategies for preventing, diagnosing, and treating ocular disorders.